2010
DOI: 10.1080/08927010903515122
|View full text |Cite
|
Sign up to set email alerts
|

Induction of halogenated vesicle transport in cells of the red seaweedLaurencia obtusa

Abstract: In clones of the red alga Laurencia obtusa, the frequency of vesicle transport from corps en cerise (CC) to the cell wall region was evaluated in response to differences in temperature, irradiance, desiccation, bacterial fouling, and bromine (Br) availability. In addition, the morphology of the corps en cerise was analyzed. Traffic of vesicles was induced by exposing L. obtusa to low temperatures and variations in irradiance. It was also verified that bacterial fouling induced vesicle traffic. Under high tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 37 publications
3
35
0
1
Order By: Relevance
“…Until recently, Laurencia obtusa has been widely reported for the Brazilian coast (Joly, 1965;Oliveira Filho, 1969, 1977Pedrini, 1980;Yoneshigue, 1985;Paes e Mello & Pereira, 1990;Figueiredo Creed & Yoneshigue-Valentin, 1997;Pinheiro-Joventino et al, 1998;Da Gama et al, 2002;Paradas et al, 2010). In addition, specimens have been reported from Brazil that have similar morphology to L. obtusa but have been identified as L. microcladia Ku¨tzing (Joly, 1965;Oliveira Filho, 1969;Cordeiro-Marino, 1978;Figueiredo et al, 2004), L. heteroclada Harvey (Oliveira Filho, 1969), L. composita Yamada (Oliveira Filho, 1969; Paes e Mello & Pereira, 1990), L. arbuscula Sonder (Cordeiro-Marino et al, 1983;Fujii, 1990), L. scoparia J. Agardh (Cordeiro-Marino et al, 1983;Fujii, 1990), L. majuscula (Harvey) A.H.S.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, Laurencia obtusa has been widely reported for the Brazilian coast (Joly, 1965;Oliveira Filho, 1969, 1977Pedrini, 1980;Yoneshigue, 1985;Paes e Mello & Pereira, 1990;Figueiredo Creed & Yoneshigue-Valentin, 1997;Pinheiro-Joventino et al, 1998;Da Gama et al, 2002;Paradas et al, 2010). In addition, specimens have been reported from Brazil that have similar morphology to L. obtusa but have been identified as L. microcladia Ku¨tzing (Joly, 1965;Oliveira Filho, 1969;Cordeiro-Marino, 1978;Figueiredo et al, 2004), L. heteroclada Harvey (Oliveira Filho, 1969), L. composita Yamada (Oliveira Filho, 1969; Paes e Mello & Pereira, 1990), L. arbuscula Sonder (Cordeiro-Marino et al, 1983;Fujii, 1990), L. scoparia J. Agardh (Cordeiro-Marino et al, 1983;Fujii, 1990), L. majuscula (Harvey) A.H.S.…”
Section: Introductionmentioning
confidence: 99%
“…Their shape varies from spherical, reniform to claviform, and a connection to the cell wall is frequently observed. These organelles were confirmed as the main storage site for halogenated compounds (Young et al, 1980;Salgado et al, 2008;Paradas et al, 2010). Dworjanyn et al (1999) confirmed the localization of bioactive secondary metabolites in the red alga Dilsea pulcra (Greville) Montagne in the central vesicle of gland cells using a combination of fluorescence microscopy, culture studies and quantitative chemical analyses.…”
Section: Introductionmentioning
confidence: 64%
“…These authors suggested that exocytosis specifically transports the halogenated compounds to the surface and that variations in this mechanism could result in different concentrations of the compounds on the algal surface. Paradas et al (2010) have also demonstrated that variations in temperature, irradiance level, and desiccation can influence the transport of vesicles from the CC to the cell wall region in clones of L. dendroidea (as L. obtusa).…”
Section: Introductionmentioning
confidence: 99%
“…2006, Salgado et al 2008, Paradas et al 2010 and Laurencia translucida Fujii & Cordeiro-Marino (Paradas 2013).…”
Section: Introductionunclassified
“…Concerning major advances in cell biology, it was shown that L. dendroidea transports halogenated metabolites from CC to thallus surface in response to epiphytic bacteria through vesicle traffic (Paradas et al 2010). In addition, Reis et al (2013) showed that cytoskeleton elements have a central role in this L. dendroidea defensive system.…”
Section: Introductionmentioning
confidence: 99%